An educational game for teaching osmolarity and tonicity: opinions of dental and medical students - Pessoa, Pamella Teles; Palanch, Adrianne Christine; Casale, Karina Reche; Montrezor, Luís Henrique [UNESP]; Taxini, Camila Linhares; Azevedo, Maria Antonia [UNESP]; Marcondes, Fernanda Klein [UNESP] (American Physiological Society, 2023)
In health courses, the students must be familiar with the effects of intravenous solutions on cell volume and function, a topic where there can be learning difficulties and misunderstandings. Since educational games can assist in understanding complex concepts, we created a game relating solution osmolarity and tonicity to red blood cell volume that was used in undergraduate Dentistry and Medicine courses. The students, working in groups, completed the game board by indicating the effect of the solutions on the red blood cell volume and classifying the solutions in terms of tonicity and osmolarity. The student indicated that the use of the educational game contributed to their understanding of osmolarity and tonicity. NEW & NOTEWORTHY This study describes an educational game for teaching osmolarity and tonicity, using classical red blood cell experiment results. The game was used during dialogic teaching, which was interrupted three times so that the student groups could answer questions about the experiments by completing a table describing the effects of different solutions on cell volume. According to the students’ perception, the game contributed to their understanding of osmolarity and tonicity as related to human cells.
Keywords: dialogic teaching; gamification; intravenous solution